Nursing Students’ Skills Level of Promote Safety, Physiology Integrity, Psychosocial Integrity, and Health Promotion in Pediatric Care in a Selected Health Institute in Indonesia - Windasari Aliarosa (Humanistic Network for Science and Technology (HNST), 2018)
This study aimed to determine the level of skills of nursing students in term of promote safety, physiology integrity, psychosocial integrity, and health promotion in pediatric care in a selected health institute in Indonesia. The study made used of descriptive correlational research design. The participants of the study were nursing students and their clinical instructors. Universal sampling technique was used which encompassed the total twenty-three (23) nursing students and two (2) clinical instructors who directly supervised the students in the clinical area. Frequency, percentage statistical treatment, weighted mean, T-test, and Pearson-r were used to process the result of the study. Nursing students are moderately competent in area of skills in rendering pediatric care. There were significant differences between the ratings of the nursing students level of skills in pediatric care in all of variables as rated by nursing students themselves and by their clinical instructors. And there was no significant relationship between the nursing students’ age and gender and their level of skills in pediatric care. On the contrary, there was a significant relationship between the nursing students’ GPA and their level of skill in pediatric care. The proposed pediatric care clinical focus can be adopted to enhance nursing students’ level of skills in pediatric care. Keywords: Pediatric care, Nursing student, Skill’s clinical focus